Oblikovanje čustev in vedenja z glasbo: priročnik za vzgojitelje, učitelje, svetovalne delavce, terapevte pri delu z otroki in mladostniki s čustveno vedenjskimi težavami - Habe, Katarina; Licardo, Marta (2019)
Emotional and Behavioural Regulation Through Music: Handbook for preschool teachers, elementary teachers, counsellors, therapists in work with children with emotional and behavioural problems. The manual “Emotional and behavioural regulation through music” is dedicated to experts from various professions, who work with children and adolescents with emotional behavioural difficulties (preschool and schoolteachers, consultants, therapists, etc.), who have appropriate music background and who want to use innovative ways of working with children with special needs. The manual presents an innovative approach that uses the positive effects of music activities on emotions and behaviour. In the first chapter, emotional and behavioural difficulties are defined. In the second chapter, the occurrence of these difficulties in different developmental periods are presented. A systematic review of the positive effects of music and musical activities on children and adolescents with emotional and behavioural disorders is presented in third chapter. Extensive focus on music therapy and its use when working with children and adolescents is made in the fourth chapter, following with the presentation of music-didactical games. The main part of the manual presents a practical display of musical activities, based on the elements of music therapy and musical didactic games with tracking of the affective and social-moral development. The practical part of the manual can be with some adjustments transferred to working with other groups of children/adolescents with special needs, furthermore, it can be used in teaching music in primary schools and music schools to motivate children with different approaches.
Keywords: emotional behavioral problems; teaching methods; music therapy; musical didactic games; children and adolescents